Whole genome sequencing analysis of antibiotic resistant genes of Shigella species: A systematic review and meta-analysis - Basha Ayele; Getenet Beyene; Zeleke Mekonnen; Ahmed Esmael; Abaysew Ayele; Dawit Hailu Alemayehu; Getachew Tesfaye Beyene (PLoS ONE, 2025)
Background In developing nations, Shigella species are the leading cause of epidemic dysentery, especially among children under five. Antibiotic resistance has spread quickly among Shigella species as a result of inappropriate antibiotic use, inadequacies of diagnostic facilities, unhygienic conditions, and insufficient healthcare practices. This review aimed to describe AMR genes of Shigella species analyzed globally via whole genome sequencing (WGS). Methods Relevant papers were found via a literature search using the databases of Google Scholar, Web of Science, PubMed, and Scopus. Full-text primary studies published in English, WGS, Shigella serogroup, and AMR gene statistics had to be included in the articles. The comprehensive meta-analysis software was used for data analysis. The Der Simonian–Laird random effect model was utilized and statistical heterogeneity between studies is measured by the I 2 and Cochran’s Q test. Results Of the studies, resistant genes of S. flexneri was more studied and characterized. The overall prevalence of antibiotics resistance genes was in the range of 1.7% to 46.9% with gyrA S83 L was the most frequent isolated revealed this gene as predominant in the quinolones resistant gene of S. sonnei. It was followed by mphA (resistant to macrolides) for S. flexneri, and sul2 (resistant to folate synthesis inhibitors) for S. dysenteriae and S. boydii . Pooled prevalence of AMR gene in Shigella species significantly varied among the studies (p = 0.001). There was no significant amount of heterogeneity in S. bodyii (Q (4)) =1.938. p = 0.747, I 2 = 0%) however in S. flexneri (I 2 = 63%) and S. sonnei (I 2 = 84%) showed high heterogeneity within the studies. Conclusion Generally, there was considerable variation in the pooled prevalence of the AMR gene in Shigella species among the studies, with S. flexneri and S. sonnei showing the highest levels of heterogeneity. The effectiveness of treatment is seriously threatened by Shigella’s resistance to antibiotics. Therefore, it is imperative that Shigella species resistance be continuously monitored globally.